Pengaruh Customer Engagement Terhadap Customer Satisfaction dan Brand Trust Pada Produk Skincare Skintific - Islami, Heni Widya; Winata, A. Yahya Surya (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
This research aims to find out whether there is an influence of customer engagement on customer satisfaction and brand trust in skintific skincare products.This research is quantitative research with data collection techniques using questionnaires. The sample in this study consisted of 120 students from the Facultyof Economics and Business, Trunojoyo Madura University.Using SEM PLS 4.0 analysis tools. The results of the descriptive research show that customer engagement towards brand trust can be accepted and has a positive and significant effect. Meanwhile, customer engagement on customer satisfaction can be accepted and has a positive and significant effect, so the variable customer satisfaction on brand trust can be accepted and has a positive and significant effect, and the results of the research can also have an indirect effect on the variables of customer engagement and customer satisfaction on brand trust simultaneously. or together have an influence on brand trust in skintific skincare products.